Two‐component modified polyurethane sealant for insulating glass: Design, preparation, and application. Issue 46 (12th July 2019) - Li, Wan; Liu, Xingjiang; Wu, Jinbi; Wu, Linzhi; Sun, Ailing; Wei, Liuhe
ABSTRACT: A new two‐component modified polyurethane (PU) sealant was designed and synthesized for insulating glass. This sealant was designed based on a crosslinked reaction between a p ‐chlorophenol‐blocked PU pre‐polymer (Pre‐polymer2 ) in Component A and a poly‐functional hyperbranched polyamine polymer (polyamide resin 300 # ) in Component B. During the synthesis of Pre‐polymer2, Fourier transform infrared spectral analysis was used to track the process, and the optimal reaction time and temperature were 1.5 h and 80 °C, in the presence of 4, 4′‐diphenylmethane diisocyanate (MDI). Different curing agents also used as deblocking agents were screened and it was found that polyamide resin 300 # was a good candidate for the curing reaction. In addition, the low‐temperature curing rate was also improved by using dibutyltin dilaurate (DBTDL) and organobentonite together as a composite catalyst. Finally, the prepared two‐component modified PU sealant for insulating glass was successfully used in an assembly line with good performance. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48219. Abstract :